Time Is Power: Rethinking Meritocratic Political Selection in China. (1st March 2021) - Zeng, Yu; Wong, Stan Hok-wui
Abstract: Whether local officials in China are promoted on a meritocratic basis has been the subject of long-standing debate. Merit is commonly gauged by a leader's ability to deliver local GDP growth. Although some find economic performance to be a strong predictor of the career success of local leaders, we argue that the existing measure, which focuses on the promotion outcome of a single career step, is problematic because the career success of individual local leaders is seldom determined by a single promotion, or the lack thereof. We propose an alternative measure that is more suitable for China's political context: the length of time until promotion. Analysing the time it takes to gain promotion for four types of local leaders, we find that good economic performance is associated with a shorter time until promotion. However, the cumulative time-reducing effect of economic performance is far from significant, as it is generally insufficient to help local leaders overcome the age ceiling for promotion.